Teaching New Graduate Nurses About Infusion Therapy in a Nurse Residency Program. Issue 1 (January 2015) - McPhee, Kim
<x xml:space="preserve">Abstract</x> The purpose of this article is to describe how the concept of infusion nursing was incorporated into orientation for new graduate nurses at an academic medical center in the Midwest. Strategies were identified based on their unique learning needs and a desire to instill safe infusion practices early in their nursing careers. (A Supplemental Video Abstract for this article is available at http://links.lww.com/JIN/A64.)